Hubungan Karakteristik Perawat Dan Beban Kerja Dengan Kelelahan Kerja Perawat Di Ruang Rawat Inap RSUD Kota Tanjungpinang - Dame Maria Pakpahan; Fitriany Suangga; Rizki Sari Utami (Jurnal Rumpun Ilmu Kesehatan, 2024)
A nurse is someone who works and provides excellent and quality service 24 hours a day, so a nurse must be in good physical condition. The condition of the body which should be in the rest phase must be conditioned on working conditions which can result in work stress and end in work fatigue. Work fatigue is a tired condition felt by a person which is also characterized by a decrease in work productivity. Workload is the volume of work of nurses in a hospital unit. This study aims to determine the relationship between nurse characteristics and workload with work fatigue in inpatient rooms at the Tanjungpinang City Regional Hospital. The design of this research is cross sectional. The sample in this study was 86 patients treated at the Tanjungpinang City Regional Hospital using a total sampling technique and the data were analyzed using the chi square test. The results show that there is a relationship between workload and the level of fatigue in inpatient nurses at Tanjungpinang City Regional Hospital with a p value of 0.000. It is recommended that nurses should carry out Benson therapy after providing nursing care so that the level of fatigue can be reduced, understand the work and duties of nursing so that nurses can carry out their duties according to applicable regulations, and make the best use of rest time.